Through the eyes of yours - Affandi, Salwani; Affandi, Nur Afiqah; Mohamad Azmin, Nur Azwani; Azlan, Nik Noor Afizah; Abdullah, Sholehah; Ismail, Fathiyah; Abdul Manaf, Suhaily Maizan; Hamzah, Siti Fatimah Mardiah (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2022)
I used to learn about the solar system and how the planets orbited the sun when I was in school. One day, I noticed my son Fahmi watching YouTube Kids: Kids Learning Tube channel. The video was about "The stars and their sizes in comparison." It was entertaining to watch him sing, dance, draw, and color while watching his favorite YouTube channel. According to the video, there are a lot more stars in the universe that are larger than the sun. Suddenly, he questioned, "Mama, do you know how many Earths can fit into Jupiter?" and "do you know how many Earths can be swallowed by The Sun?" Errrr... I was flabbergasted, and I had no idea what he was asking me about. It shocked me and I was not sure whether to laugh or to cry for myself for not knowing the answers. LOL. Then I realized, I hadn't learned much about Allah's creations wholeheartedly all this while.